Platelet count and sleep quality in immune thrombocytopenia: correlation with 5-hydroxytryptamine and therapeutic implications of platelet-5-HT-melatonin axis dysregulation - Jiao, Yingying; Fan, Wenxuan; Wang, Yu; Qin, Yuehong; Zhang, Yujiao; Ye, Jieyu (Frontiers in Neurology, 2025)
BackgroundImmune thrombocytopenia (ITP) disrupts platelet homeostasis via autoimmune mechanisms, yet its systemic effects beyond bleeding risk remain poorly characterized. Sleep disturbances are frequently reported in ITP patients, but the relationship between thrombocytopenia, serotonergic signaling, and sleep architecture remains undefined. This study investigates whether platelet dynamics modulate sleep quality through the “platelet-5-HT-melatonin axis” and explores therapeutic implications of this axis in ITP.MethodsIn a prospective longitudinal cohort of 87 ITP patients (baseline platelet count: 28.7 ± 15.2 × 109/L) and 71 healthy controls, sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI) at baseline and after 12 weeks of standard glucocorticoid therapy. Subgroup analysis stratified patients by platelet count (<50 × 109/L vs. ≥50 × 109/L). Circulating 5-hydroxytryptamine (5-HT) levels were quantified in 42 patients via ELISA. Longitudinal changes in sleep metrics and 5-HT were analyzed using linear mixed-effects models (LMMs), with Cohen’s d effect size to assess clinical relevance. Correlations between platelet count, PSQI scores, and inflammatory markers (hs-CRP, IL-6) were explored.ResultsAt baseline, ITP patients had significantly higher PSQI scores than controls (12.4 ± 3.8 vs. 6.2 ± 2.1, p < 0.001), mainly reflecting impaired efficiency (d = 0.89), prolonged latency (d = 0.75), and daytime dysfunction (d = 0.92). Platelet count inversely correlated with PSQI (r = −0.223, p = 0.04), and 68% of patients with <50 × 109/L platelets had severe sleep disturbance (PSQI >10). After treatment, patients achieving platelet normalization (>100 × 109/L) showed significant improvements in sleep latency (−23.5%, p = 0.008), duration (+18.2%, p = 0.02), and 5-HT levels (+42.7%, p < 0.001), alongside reduced fatigue scores. Mechanistically, thrombocytopenia impaired 5-HT uptake and reduced nocturnal melatonin secretion, while elevated hs-CRP and IL-6 indicated inflammation-driven hypothalamic-pituitary-adrenal axis dysregulation.ConclusionITP-associated thrombocytopenia disrupts sleep architecture through serotonergic dysregulation and chronic inflammation. Standard glucocorticoid therapy not only restores platelet counts but also ameliorates sleep quality and fatigue, highlighting the therapeutic potential of platelet-targeted interventions for comorbid sleep disorders. These findings advocate for routine sleep assessment in ITP management and integration of 5-HT-modulating strategies into comprehensive care frameworks to address the hematologic-immunologic-sleep axis.